ANALISIS PENGARUH KEPUASAN GAJI, KEPUASAN BEBAN KERJA, KEPUASAN KARIR DAN KEPUASAN PENILAAN KINERJA TERHADAP INTENSIKELUAR PADA KARYAWAN RND DI PT SAMSUNG ELECTRONICS INDONESIA - , Sukma Jati ([Yogyakarta] : Universitas Gadjah Mada, 2014)
High rate of turnover leads to adverse effect to an organization, such as decrease of product quality cause of a lot of product defect and delay in product development process and financial loss of employee recruitment and training programs. This study aims to analyze the effect of salary satisfaction variable, work load satisfaction, career satisfaction and performance appraisal satisfaction on turnover intentions. Data is obtained by giving questionnaires to 212 employees of Research and Development department of PT. Samsung Electronics Indonesia. Data is analyzed using software SPSS 21.0 for Windows. The result of research shows that salary satisfaction, work load satisfaction, career satisfaction and performance appraisal satisfaction has a significant effect on turnover intentions. Therefore, in order to push the turnover intentions in a low number, the company needs to take efforts to improve salary satisfaction, work load satisfaction, career satisfaction and performance appraisal satisfaction of the employees. For the next study is expected to explore other variables such as organizational commitment, organizational culture, leadership, work environment and other variables that might have an influence on turnover intentions of employees in a company.